A new healing strategy for metals: Programmed damage and repair. (1st October 2022) - Arseenko, Mariia; Hannard, Florent; Ding, Lipeng; Zhao, Lv; Maire, Eric; Villanova, Julie; Idrissi, Hosni; Simar, Aude
Abstract: Self-healing strategies aim at avoiding part repair or even replacement, which is time consuming, expensive and generates waste. However, strategies for metallic systems are still under-developed and solid-state solutions for room temperature service are limited to nano-scale damage repair. Here we propose a new healing strategy of micron-sized damage requiring only short and low temperature heating. This new strategy is based on damage localization particles, which can be healed by fast diffusing atoms of the matrix activated during heat treatment. The healing concept was successfully validated with a commercial aluminum alloy and manufactured by Friction Stir Processing (FSP). Damage was demonstrated to initiate on particles that were added to the matrix during material processing. In situ 2D and 3D nano-imaging confirmed healing of the damaged material and showed that heating this material for 10 min at 400°C is sufficient to heal incipient damage with complete filling of 70% of all damage (and up to 90% when their initial size is below 0.2 µm). Furthermore, strength is retained and the work of fracture of the alloy is improved by about 40% after healing. The proposed Programmed Damage and Repair healing strategy could be extended to other metal based systems presenting precipitation. Graphical abstract: Image, graphical abstract